The impact of pharmacist-led medication therapy management on medication adherence in patients with type 2 diabetes mellitus: a randomized controlled study - Erku DA; Ayele AA; Mekuria AB; Belachew SA; Hailemeskel B; Tegegn HG (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Poor adherence to antidiabetic medications leads to a higher rate of hospital admissions and adverse health outcomes in type 2 diabetes mellitus patients. Objective: This study aims to evaluate whether a pharmacist-led medication therapy management, compared to the usual care, could enhance medication adherence and reduce hospital admission in patients with type 2 diabetes mellitus. Methods: A prospective randomized controlled study was conducted in patients with type 2 diabetes mellitus from February 1 to July 30, 2016. Patients in the control group (n=65) received the usual care while patients in the intervention group (n=62) received a personalized pharmacotherapeutic care plan and diabetes education. The two groups were compared by repeated measure ANOVA at 3 and 6‐months with medication adherence (using Morisky medication adherence scale) and number of hospital admissions as the main outcome variables. Results: A total of 127 patients were included in the study. A marked and statistically significant increase in medication adherence from baseline to 3 and 6 months were noted in the intervention group (increased from 9.2% at baseline to 61% at 6 month) compared with the control group (increased from 13.2% at baseline (to 30.2% at 6 month; p-value<0.01). Furthermore, at the 6-month follow-up, only 23 patients in MTM group with poorly controlled blood glucose levels resulted in hospital admissions compared to 48 patients in non-MTM group, resulting in a 52.1% fewer hospital admissions (p< 0.001). Conclusions: The findings of this study implied that pharmacist-led medication therapy management might improve medication adherence and reduce number of hospitalizations in patients with type 2 diabetes mellitus. Hence, policies and guidelines should be in place in order for clinical pharmacists to fully engage in patient care and improve the medication therapy outcomes.